(untitled) (Research, Society and Development, 2021)
In the middle of the 21st century, the problem of dropping out and dropping out of school has not yet been mitigated and, consequently, from what has been determined, it will still take a long time to be extinguished from formal education. This work aimed to understand how school dropout and dropout occurs, what are the challenges faced by educational institutions in order to limit their progress and identify their causes and consequences. The methodology used in accordance with the collection procedures was a Case Study, linked to a field research, with the research site being the Municipal School “João Mendonça”, located in the City of Teixeira de Freitas-Bahia. As for the nature of the data, it was configured as a qualitative research. The subjects of the research were students of Basic Education (Elementary Education II and Education of Youth and Adults-EJA), with a time frame from the years 2014 to 2018. The research was justified so that it is possible to know and work in the eradication of this problem that affects educational institutions, affecting children, adolescents, young people and adults, in spite of the national legislation, with public policies related to this problem. There was no intention here to exhaust the theme, but to bring a reflection with the theoreticians, researchers and educators who have already been dealing with the theme and that the dissemination of this evil that affects education in Brazil is extinguished once and for all.